Methods For Developing Ecological Education Grounded In The Heritage Of Eastern Scholars And National Values - Turakulova Visola (European International Journal of Pedagogics, 2025)
This article proposes and examines a methodology for developing school-level ecological education that draws substantively on the intellectual heritage of Eastern scholars and on living national values. While global frameworks for Education for Sustainable Development (ESD) emphasize competencies such as systems thinking, future thinking, and values-based decision making, their classroom realization often lacks culturally resonant anchors. To address this gap, we articulate a heritage-integrated model that translates core ideas from scholars such as Al-Farabi, Ibn Sina (Avicenna), Al-Biruni, Al-Khwarizmi, and Alisher Navoi into didactic strategies aligned with contemporary ESD outcomes. The model combines value-culturological and ethnopedagogical approaches with project-based learning, inquiry, and service-learning in community settings. A mixed-methods pilot with lower-secondary students tested a 12-week program embedded across technology, literature, and geography lessons. Quantitative measures included a curriculum-aligned knowledge test, an environmental attitudes scale, and a self-reported pro-environmental behavior index; qualitative sources comprised classroom observations, artifact rubrics, and student reflection journals. Results indicated statistically and educationally significant gains in knowledge and dispositions, with qualitative evidence of identity-mediated internalization of ecological norms. We discuss how heritage-based framing strengthened meaning, elevated ethical dimensions, and facilitated cross-disciplinary transfer, while also noting cautions against romanticization or essentialism. The paper concludes with implications for teacher professional development, assessment design, and scaling within national curricula.